Microstructural-property relationships of PZT - Qiu, Wei. (2008)
Characterization of pure and Pb(Y1/2Nb1/2)O3-doped Pb(Zr0.53/Ti0.47)O3 (PZT) with th morphotropic phase boundary composition has been undertaken in this study.